Exploring Linguistic Innovations Within Chinese Internet Slang in Language and Social Media - Yahui He (Journal of Linguistics and Communication Studies, 2024)
This paper explores the dynamic landscape of Chinese internet slang and digital culture, analyzing its evolution, impact, and challenges. Through case studies and critical analysis, it delves into the linguistic innovations, cultural implications, and societal dynamics shaping digital discourse in contemporary China. The study investigates the emergence of new slang terms, the role of digital platforms in fostering online communities, and the complexities of navigating privacy concerns and regulatory frameworks. By examining future directions and implications, the paper seeks to offer insights into the transformative potential of Chinese internet slang and digital culture in shaping communication, identity, and social interactions in the digital age.